Bait Formulations from the Mixture of Degraded Wood and Wastepaper for Termite Control - Musrizal Muin; Astuti Arif; Siti Nuraeni; Wa Ode F Zohra (Masyarakat Peneliti Kayu Indonesia, 2015)
The bait formulation from the mixture of organic wastes for termite (Coptotermes sp) control was evaluated in laboratory and field tests. Four formulations were prepared by equally mixing based on dried weights, i.e. the mixture of degraded pine wood and HVS wastepaper, degraded pine wood with HVS and newsprint wastepaper, degraded pine wood with HVS and cardboard wastepaper, and the mixture of degraded pine wood with HVS, newsprint, and cardboard wastepaper. Boiled soybean water was used as an additional substance of the formulation. The termite survival rate and food transfer were evaluated using no-choice test. The food transfer was studied using test samples dyed with 0.1% Nile Blue A. The food formulations were also subjected to field test for six weeks to evaluate the termite attacks. The results showed that the highest food transfer efficiency was found for degraded pine wood and HVS wastepaper formulation, however, the survival rate was not significantly different among the formulations. The field test proved that the mixture formulation of degraded pine wood with HVS and cardboard wastepaper as well as that of degraded pine wood with HVS, newsprint, and cardboard wastepaper were attacked by termites to the failure level.Keywords: bait formulation, Coptotermes sp., food transfer efficiency, survival rate, termite control